Search for Higgs boson pair production in the γγbb[bar] final state using pp collision data at √s = 8 TeV from the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Dunford, Monica; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; Lang, Valerie; Meier, Karlheinz; et al. (Physical review letters, 2015)
Searches are performed for resonant and nonresonant Higgs boson pair production in the γγb¯b final state using 20  fb−1 of proton-proton collisions at a center-of-mass energy of 8 TeV recorded with the ATLAS detector at the CERN Large Hadron Collider. A 95% confidence level upper limit on the cross section times branching ratio of nonresonant production is set at 2.2 pb, while the expected limit is 1.0 pb. The difference derives from a modest excess of events, corresponding to 2.4 standard deviations from the background-only hypothesis. The limit observed in the search for a narrow X→hh resonance ranges between 0.7 and 3.5 pb as a function of the resonance mass.
Im Titel steht der zweite Buchstabe b mit einem Oberstrich
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A. Baas, O. Brandt, M. Dunford, P. Hanke, J. Jongmanns, E.-E. Kluge, A. Kugel, V. Lang, K. Meier, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und 2863 weitere Personen]
Gesehen am 12.07.2021